Instrumental Variable Estimates of the Effect of Management Practices on Firm Performance in Korean Firms. - Chang, Jieun; Kang, Youngho (Journal of Labor Research, 2019)
Policy makers as well as entrepreneurs pay much attention to the success of firms. This is because the performance of firms can promote directly and indirectly the economic growth in a country. For instance, after financial crisis in 1997, the Korean economy experienced the rapid recovery. It is recognized that the improvement of firm performance has played a crucial role in such recovery. We focus on the determinants of improving the Korean firm total factor productivity (TFP) because TFP can explain performance not explained by inputs a firm employs. This paper suggests management practices as one of crucial factors to improve firm TFP. For empirical analysis, we use an instrumental variable approach by using a set of four firm-level instrumental variables including motivations for organizational change, large-scale organizational change, empowerment, and IT investment during the past organizational change. The results of the instrumental variable estimation show that better management practice leads to a higher level of firm TFP, statistically significantly; whereas the effect of management practices is statistically insignificant in the ordinary least square estimation.